Fonctions discursives des routines de référence dans le débat parlementaire (Philology, 2024)
The text analyzes the discursive functions of several routines with referential meaning in oral speeches during debates in the European Parliament. The study fits into the field of transdisciplinary phraseological studies of specialized texts carried out in France. The routines described are excerpted from an electronic corpus by applying the repeatability principle with statistical significance.Routines are lexical word combinations that stand out with a semi-permanent character and with a high frequency of use and regularity within a given discursive genre, possessing certain socio-professional and discursive characteristics. The phrases sur ce point, à cet égard, comme je l’ai dit, comme vous le savez, à ce titre, and pour cela contain anaphoric and deictic markers that give them a specific discursive function, namely to direct the audience’s attention to a piece of information which is important for reaching consensus, the main communicative goal of the speaker. The oral nature of the utterance and the specificity of dialogism require the application of a certain discursive strategy, which includes the use of similar expressions with a referential meaning. Functioning as parenthetical expressions, routines evoke interruptions, pauses, and repetitions that create relations of salience and fix attention on significant facts. The speaker manages to transform intralocutive dialogism into interlocutive dialogism, to turn the construction of the discourse into co-construction thanks to the audience’s involvement based on shared knowledge.
Keywords: dialogism; phraseology; discourse; oral speech